1999
DOI: 10.1016/s0002-9440(10)65189-9
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cell Proliferation and Regrowth after Mechanical Injury in Vitro Are. Egr-1/NGFI-A-Dependent

Abstract: Smooth muscle cell (SMC) proliferation is a key event in renarrowing of blood vessels after balloon angioplasty. Mechanical injury imparted to the arterial wall in experimental models induces the expression of the immediate-early gene , egr-1. Egr-1 binds to and activates expression from the proximal promoters of multiple genes whose products can , in turn , influence the vascular response to injury. Here , we used antisense strategies in vitro to inhibit rat vascular SMC proliferation by directly targeting Eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 40 publications
5
51
0
Order By: Relevance
“…Previous reports indicated that transcription factors Egr-1 and c-Fos play a key regulatory role in SMC proliferation and repair following injury [27]. As shown in Fig.…”
Section: Mechanical Injury-induced Egr-1 and C-fos Up-regulation Was mentioning
confidence: 72%
See 2 more Smart Citations
“…Previous reports indicated that transcription factors Egr-1 and c-Fos play a key regulatory role in SMC proliferation and repair following injury [27]. As shown in Fig.…”
Section: Mechanical Injury-induced Egr-1 and C-fos Up-regulation Was mentioning
confidence: 72%
“…In injured vascular cells, Egr-1 is rapidly activated and found to be involved in profound chemotactic and mitogenic effects, which may contribute to the structural remodeling that typically occurs in the pathogenesis of vascular diseases [7,43]. Antisense oligonucleotides or DNA enzymes targeting Egr-1 inhibited SMC proliferation after mechanic injury in vitro [6,27,30,44]. These DNA enzymes also block Egr-1 induction and neointima formation in a rat carotid angioplasty model [30] and after stenting pig coronary arteries in vivo [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In systemic vessels, the importance of Egr-1 expression during vascular remodeling has been confirmed given that neointima formation is reduced when Egr-1 expression is blocked. [33][34][35][36] In addition, these studies demonstrate that Egr-1-induced neointima formation is mediated through both proliferative and inflammatory pathways. [33][34][35][36] Taken together, this is the first study to demonstrate the spatiotemporal correlation between increased Egr-1 expression and increased pulmonary blood flow, as an inductor of neointimal development.…”
Section: Egr-1 Transcription During Pulmonary Vascular Remodelingmentioning
confidence: 68%
“…[33][34][35][36] In addition, these studies demonstrate that Egr-1-induced neointima formation is mediated through both proliferative and inflammatory pathways. [33][34][35][36] Taken together, this is the first study to demonstrate the spatiotemporal correlation between increased Egr-1 expression and increased pulmonary blood flow, as an inductor of neointimal development. These data suggest that Egr-1 may be able to initiate and maintain the process of neointimal development in flow-associated PAH and therefore also justifies further exploration of the exact role of Egr-1 in pulmonary vascular remodeling in PAH.…”
Section: Egr-1 Transcription During Pulmonary Vascular Remodelingmentioning
confidence: 68%